2022
DOI: 10.21203/rs.3.rs-2294169/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Titania Nanotube Arrays Surface Anodization and Various Human Cell Line Models Adherence Profiles

Abstract: Titania nanotube arrays (TNA) have high biocompatibility, less toxicity, and a large surface area per volume; thus, TNA offer great potential in biomedical applications. Interactions between micro environment and cell on the TNA surface are intensively investigated regarding cell attachment and interaction. Anodization was used to create a highly ordered nano-porous oxide layer with nano-sized pores on the surface of the titanium. This process was carried out at 30 V with a sweep rate of 1 V/sec for a differen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…8,9 TNA have been described previously with unique surface roughness properties, contact angle, and surface energy that is favorable for cell interaction. [10][11][12][13][14][15] Studies have reported that TNA nanosurface provides better cell spreading and differentiation behavior. Most notably, this study has provided insights into understanding the cell-TNA mechanotransduction response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 TNA have been described previously with unique surface roughness properties, contact angle, and surface energy that is favorable for cell interaction. [10][11][12][13][14][15] Studies have reported that TNA nanosurface provides better cell spreading and differentiation behavior. Most notably, this study has provided insights into understanding the cell-TNA mechanotransduction response.…”
Section: Introductionmentioning
confidence: 99%
“…TNA have been described previously with unique surface roughness properties, contact angle, and surface energy that is favorable for cell interaction 10–15 . Studies have reported that TNA nanosurface provides better cell spreading and differentiation behavior.…”
Section: Introductionmentioning
confidence: 99%